Evaluating the attitudes and behavior of Hong Kong medical students toward receiving the COVID-19 vaccine - Nicole T. Y. Ngai; Christopher C. H. Yip; J. R. Khoo; Siddharth Sridhar (Taylor & Francis Group, 2022)
Getting vaccinated against SARS-CoV-2 lowers the risk of severe infections. In Hong Kong, two vaccine types are offered: CoronaVac by Sinovac Biotech (Sinovac), and Comirnaty by BioNTech-Fosun Pharma (BioNTech). However, a low vaccine uptake rate is observed. This study primarily aimed to determine the population of medical students who underwent COVID-19 vaccination, and to identify factors associated with their decision on timing and vaccine type. Current medical students from The University of Hong Kong (HKU) were invited to participate in this cross-sectional survey study from 16 September to 31 December 2021. The main outcome measures were the vaccine uptake rate, primary reasons for vaccine-seeking behavior, vaccine hesitancy and vaccine preference, as well as information sources. All questions were of a multiple-choice format, with a free response option for questions pertaining to reason exploration. Overall, 214 medical students participated in the study, with all questionnaires analyzed. Amongst the 98.1% that completed 2 doses, 93.4% selected BioNTech and 6.6% selected Sinovac. Significant associations were observed between year groups and vaccine timing (p = 0.00989). The primary reason to seek vaccination was immunity against COVID-19 (53.5%), while the fear of potential side effects (61.6%) accounted for vaccine hesitancy. The BioNTech vaccine was favored for its higher efficacy against COVID-19 (87.4%). Information sources were mainly from HKU professors (64.6%) and social media (59.9%). The study found a high vaccine uptake rate amongst medical students, contrary to the situation observed in the Hong Kong general population at the time of the study.